2018
DOI: 10.1186/s11782-018-0032-z
|View full text |Cite
|
Sign up to set email alerts
|

Cross-listing and CSR performance: evidence from AH shares

Abstract: This study investigates the association between corporate social responsibility (CSR) performance and cross-listing. In a clean setting where a change in CSR performance can be attributed to the cross-listing, we find a statistically significant and economically meaningful increase in CSR performance for the cross-listed firms. Moreover, such an increase comes mostly in technical CSR, which targets the firms' primary stakeholders. We also find that the positive association between cross-listing and CSR improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 78 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…The most potent stakeholder (the government) facilitates SOEs during financial distress for their CSR involvement [72,73], and thus CSR leads to better financial performance of firms [58]. However, Li et al [79] found that the link of CSRP-CFP is weaker in SOEs as compared with non-SOEs, and highlighted several reasons for this discrepancy. First, the objective of SOEs includes social aims along with economic goals.…”
Section: Hypothesismentioning
confidence: 99%
“…The most potent stakeholder (the government) facilitates SOEs during financial distress for their CSR involvement [72,73], and thus CSR leads to better financial performance of firms [58]. However, Li et al [79] found that the link of CSRP-CFP is weaker in SOEs as compared with non-SOEs, and highlighted several reasons for this discrepancy. First, the objective of SOEs includes social aims along with economic goals.…”
Section: Hypothesismentioning
confidence: 99%
“…However, research is lacking on the validity of measuring CSR performance and disclosure quality, as well as the convergent validity between these scores. In this paper, a comparative and quantitative analysis was performed for the period 2010-2017, and the following results were obtained: (1) Based on a comparison of the rating methods, information sources, and other factors, RKS is more suitable for measuring the CSR disclosure quality, while Hexun is more suitable for measuring the CSR performance; (2) based on a Spearman correlation analysis, the convergent validity between these two scores is very low, particularly after 2013; and (3) the sub-indicator weights of the RKS system always maintain a high stability, whereas those of the Hexun system suffer from severe fluctuations starting in 2013.Sustainability 2019, 11, 3921 2 of 20 mechanisms of economic consequences [20][21][22][23], the drivers of CSR performance [24][25][26][27][28][29], and economic consequences [30][31][32][33][34][35]; and (2) the HX score is used only as a proxy for the CSR performance level, such as in research on the drivers of CSR performance [36][37][38][39][40] and the economic consequences of CSR performance [19,33,[41][42][43]. Some studies even use the level-1 sub-indicator of the HX score, the environmental dimension HXE, to score a firm's environmental performance level [44,45].Sustainability 2019, 11, x FOR PEER REVIEW 2 of 21 also for CSR performance levels, such as in research on the drivers of CSR disclosure quality [16][17][18][19], the mechanisms of economic consequences [20][21]…”
mentioning
confidence: 99%
“…Sustainability 2019, 11, x FOR PEER REVIEW 2 of 21 also for CSR performance levels, such as in research on the drivers of CSR disclosure quality [16][17][18][19], the mechanisms of economic consequences [20][21][22][23], the drivers of CSR performance [24][25][26][27][28][29], and economic consequences [30][31][32][33][34][35]; and (2) the HX score is used only as a proxy for the CSR performance level, such as in research on the drivers of CSR performance [36][37][38][39][40] and the economic consequences of CSR performance [19,33,[41][42][43]. Some studies even use the level-1 sub-indicator of the HX score, the environmental dimension HXE, to score a firm's environmental performance level [44,45].…”
mentioning
confidence: 99%
“…Shi et al [28] highlights the positive association of improvement efforts within the market share of entities. The improvement of CSR is more obvious for companies with poor corporate governance.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Grid of CSR Perceptions-Observations of International Experts on CSR Regarding Economic Theories and Concepts; Source[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
mentioning
confidence: 99%